2015
DOI: 10.5455/bcp.20130713091314
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Onset Obsessive-Compulsive Disorder: Clinical Features, Comorbidity, and Associated Factors

Abstract: Objective:The prevalence rate of obsessive-compulsive disorder (OCD) was found to be higher in women during pregnancy and puerperium than that estimated in the general population. Additionally, the symptomatology of OCD shows several variations during the lifetime of women. Objective of the current study was to examine the clinical characteristics and comorbidity with other anxiety and mood disorders of pregnancy-onset obsessive-compulsive disorder (POCD) and to investigate factors related to POCD. Method: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Observations have always been made that some kind of relationship exists between OCD and anxiety disorders. For instance, anxiety disorders are one of the disorders that are commonly comorbid with OCD (Kaya et al, 2015). Kaya et al (2015) stated that generalised anxiety disorder was the most prevalent comorbid disorder among their patient sample with pregnancy onset OCD.…”
Section: Pregnancy-related Anxiety and Prenatal Ocdmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations have always been made that some kind of relationship exists between OCD and anxiety disorders. For instance, anxiety disorders are one of the disorders that are commonly comorbid with OCD (Kaya et al, 2015). Kaya et al (2015) stated that generalised anxiety disorder was the most prevalent comorbid disorder among their patient sample with pregnancy onset OCD.…”
Section: Pregnancy-related Anxiety and Prenatal Ocdmentioning
confidence: 99%
“…For instance, anxiety disorders are one of the disorders that are commonly comorbid with OCD (Kaya et al, 2015). Kaya et al (2015) stated that generalised anxiety disorder was the most prevalent comorbid disorder among their patient sample with pregnancy onset OCD. They postulated that the high rate of the disorder may have been related to the pregnancy itself.…”
Section: Pregnancy-related Anxiety and Prenatal Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…For some women, symptoms may worsen postpartum, in a matter of days after childbirth [50]. OCD symptoms may also appear for the first time during pregnancy [51,52], with onset particularly likely in the first and second trimesters [53]. Also, pregnancy may correspond to a worsening of symptoms in those with pre-existing cases.…”
Section: Introductionmentioning
confidence: 99%
“…During pregnancy, estradiol levels gradually increase over the course of the 9-month period. Interestingly, a study by Kaya et al [150] found that the onset of pregnancy-related OCD was much more common in the first and second trimesters, which are characterized by comparatively lower estradiol levels than the third trimester. The early postpartum period is known to involve as much as a 1,000-fold drop in estradiol levels compared to the pregnant state [37] .…”
Section: Hormonal Modulation Of Oc Symptomsmentioning
confidence: 99%